Talent retention in the green economy strategies for a sustainable workforce - Ibrahim Khalil Ibrahim; Maysoon Abdulghaini; Aeda Hadi Saleh; Alaa Jassim Salman; Khalid Waleed Nassar Almansoori (Environment and Social Psychology, 2025)
Talent retention is a critical issue in the green economy because companies act between the goals of sustainability and the stability of the workforce. The study will be targeted at defining what makes employees stick to the company in the context of the sustainability-oriented industries where job satisfaction, career development, engagement and mentorship programs are the primary determinants. The study of the correlation between the career growth opportunities, organizational alignment and turnover intention was based on mixed method research design that involved data gathering among 500 staff members working in the renewable energy, sustainable manufacturing and eco-agriculture industry. The respondents on the formal mentoring programs were found to have responded with an increase of 21.1 in job satisfaction and a significant drop in the turnover rates, which shows that the career development program and mentorship are highly effective in employee retention. Moreover, sectoral draw depicts that the area with the lowest turnover (6%), is renewable energy, whereas eco-agriculture works on the most turnover (12%), which faces a lack of career advancement opportunities. Another factor is engagement because the turnover of top performers (those whose engagement levels exceed 85) is less than 3% and the fact that the impact of continued commitment to the work place is associated with retention in the long term. The research observes that career development, development of leaders and well-organized mentoring should be given priority by green economy organizations in ensuring that they end up with a stable and engaged workforce. The longitudinal retention patterns and the effects of the new digital transformation on sustainable talent management is worthy of further research. By bridging these gaps, organizations will be able to develop more efficient workforce strategies which will be sustainable in the long-term as we transition to a greener economy.